2016
DOI: 10.1177/1557988316643383
|View full text |Cite
|
Sign up to set email alerts
|

The Disappearing Sperms: Analysis of Reports Published Between 1980 and 2015

Abstract: Reports regarding the changes in sperm concentration in different counties of the world are inconsistent. Furthermore, the reports that sprung up from specific epidemiological and experimental examinations did not include data of prior studies or geographical variations. The current study, following a previous report of massive fall in semen volume over the past 33 years, attempts to delineate the trend of altering sperm concentrations and factors responsible for this by reviewing article published from 1980 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(99 citation statements)
references
References 254 publications
(133 reference statements)
2
95
0
2
Order By: Relevance
“…Recently, Rolland et al 9 in their analysis showed 32% decline in sperm count from 1989 to 2005 9 . In our recent articles, we have also reported decline in semen volume 10 and sperm count 11 in males over past few decades.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…Recently, Rolland et al 9 in their analysis showed 32% decline in sperm count from 1989 to 2005 9 . In our recent articles, we have also reported decline in semen volume 10 and sperm count 11 in males over past few decades.…”
Section: Introductionmentioning
confidence: 73%
“…Recent studies on male reproductive system when brought together bring conflicting evidence to the forefront regarding sperm counts with some showing significant decline while some found no change. North America, Europe and Asia were more prone to a declining trend of sperm counts over the years whereas studies based on South America and Australia do not depict such a trend 11 . However, in this present analysis a significant decline in sperm concentration has been noted in the African population.…”
Section: Data Extraction and Data Anaysismentioning
confidence: 84%
See 2 more Smart Citations
“…Sexual dysfunction in men can be explained as the failure to accomplish normal sexual intercourse, inability to respond to erectile stimuli or sustain an erection, retarded ejaculation, decreased libido, unregulated sexual behavior etc. [7]. Innumerable synthetic products are abundantly floating in the global market with quick remedial claims.…”
Section: Introductionmentioning
confidence: 99%